2006 IEEE Electrical Performane of Electronic Packaging 2006
DOI: 10.1109/epep.2006.321189
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Embedded Package Capacitors for High Performance Components

Abstract: The ever increasing power requirements of processors and application specific integrated circuits (ASICs) impose stringent requirements on the design of Power Distribution Networks (PDNs). This paper highlights a power analysis methodology and discusses the decoupling requirements of high performance components. The advantages of embedded package capacitors in core and 1/0 decoupling will be highlighted.Introduction-The increase in power densities of high end microprocessors and ASICs creates a design challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Packaging technologies that use capaci- tors embedded in the packages [8,9] or coreless substrate packages [10] could improve the robustness against power noise.…”
Section: Modelling Practice and Evaluation For Prototype Designmentioning
confidence: 99%
“…Packaging technologies that use capaci- tors embedded in the packages [8,9] or coreless substrate packages [10] could improve the robustness against power noise.…”
Section: Modelling Practice and Evaluation For Prototype Designmentioning
confidence: 99%
“…Using this technique, the distance between the power supply pins of the LSI and the bypass capacitors can be minimized and the inductances between them reduced. There have been numerous studies on embedded technology [4]- [7]. In these references, it is mainly reported that the impedance of power distribution network can be improved by embedding capacitors into the PCB.…”
mentioning
confidence: 99%